2010
DOI: 10.1007/s00419-010-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale effects on the buckling of quadrilateral nanoplates based on nonlocal elasticity theory using the Galerkin method

Abstract: The elastic buckling behavior of quadrilateral single-layered graphene sheets (SLGS) under bi-axial compression is studied employing nonlocal continuum mechanics. Small-scale effects are taken into consideration. The principle of virtual work is employed to derive the governing equations. The Galerkin method in conjunction with the natural coordinates of the nanoplate is used as a basis for the analysis. The buckling load of skew, rhombic, trapezoidal, and rectangular nanoplates considering various geometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…In the recent decades, on the basis of the nonlocal elasticity theory proposed by Eringen, many vibration, buckling and bending studies of nanobeams [15,16] and nanoplates [17,18] have been reported. For example, Babaei and Shahidi [19] studied the static instability behavior of arbitrary quadrilateral nanoplates by taking into account the small scale effects. Ravari et al [20] incorporated nonlocal elasticity approach equations into the classical Kirchoff-plates theory to establish a nonlocal plate model which takes into account the size effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, on the basis of the nonlocal elasticity theory proposed by Eringen, many vibration, buckling and bending studies of nanobeams [15,16] and nanoplates [17,18] have been reported. For example, Babaei and Shahidi [19] studied the static instability behavior of arbitrary quadrilateral nanoplates by taking into account the small scale effects. Ravari et al [20] incorporated nonlocal elasticity approach equations into the classical Kirchoff-plates theory to establish a nonlocal plate model which takes into account the size effect.…”
Section: Introductionmentioning
confidence: 99%
“…Saadatpour and Azhari (1998) used Galerkin technique for static analysis of simply supported plates of arbitrary quadrilateral shape. Furthermore, the small-deflection stability analysis of various quadrilateral nanoplates, such as skew, rhombic, and trapezoidal nanoplates, was carried out on the basis of the Galerkin method (Babaei and Shahidi 2010). Using the general procedure of the method yields the following: …”
Section: Solutions By Galerkin Methodsmentioning
confidence: 99%
“…All of these models were based on Kirchhoff plate theory 8,12,[14][15][16][17][18][19][22][23][24][25][26][27] , Mindlin plate theory 9,11,20,[28][29][30] , and Reddy plate theory 10,13,31 . It should be noted that the Kirchhoff plate theory (KPT) is only applicable for thin plates.…”
Section: Introductionmentioning
confidence: 99%